Current Status of Antimicrobial Stewardship Programs in São Paulo Hospitals - Sato, Silvia Akemi (2021)
OBJECTIVES: Antimicrobial stewardship programs (ASPs) comprise coordinated interventions designed to improve antimicrobial use. Understanding the current structure of ASP hospitals will support interventions for the improvement of these programs. This study aimed to describe the status of ASPs in hospitals in São Paulo, Brazil. METHODS: A cross-sectional survey was conducted on the ASPs of hospitals in the state of São Paulo from March to July 2018. Through interviews by telephone or e-mail, we queried which components of the Infectious Diseases Society of America/Society for Healthcare Epidemiology of America and Centers for Disease Control and Prevention guidelines were implemented. RESULTS: The response rate was 30% (28/93 hospitals), and 26 hospitals (85%) reported having a formal ASP. The most frequently implemented strategies were antimicrobial surgical prophylaxis guidelines (100%), empiric sepsis guidelines (93%), and the presence of ASP team members during bedside rounds (96%). The least commonly implemented strategies included prior authorization for all antimicrobials (11%), pharmacokinetic monitoring, and an adjustment program for patients on IV aminoglycosides (3%). Regarding the metrics of the ASP, the most common indicator was the rate of antimicrobial resistance (77%). Eighteen hospitals evaluated antimicrobial consumption using defined daily dose, and only 29% evaluated the days of therapy; 61% of hospitals reported their results to the hospital administration and 39% to the prescribers. CONCLUSIONS: Most hospitals have a formal and active ASP, but with timely actions. We observed inconsistencies between what program leaders understand as the main objective of ASP and the metrics used to evaluate it. Part of the effort for the next few years should be to improve program evaluation metrics and to provide feedback to physicians and hospital leadership.